2014
DOI: 10.3390/ijms150611161
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations of TAP1 Gene Exon 3 Affects Gene Expression and Escherichia coli F18 Resistance in Piglets

Abstract: Firstly, our research group identified Sutai pigs’ phenotypes that exhibited extreme resistance and susceptibility to the Escherichia coli F18 respectively, and then eight ETEC (Enterotoxigenic Escherichia coli) F18-resistant piglets and eight ETEC F18-sensitive piglets were selected. Then, the TAP1 (Transporter associated with antigen processing) mRNA relative expression levels were analyzed in 11 tissues of the resistant and susceptible phenotypes. Simultaneously, we detected the genetic variations in exon 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…TAP1 plays a significant role in immune responses because of its increased expression level after infection by viruses and bacteria. Zhao et al (2014) analyzed TAP1 mRNA relative expression levels in 11 tissues from resistant and susceptible phenotypes, and found that the G729A mutation of TAP1 had a significant effect on TAP1 mRNA expression, with high expression possibly conferring resistance against E. coli F18, which confirms that the TAP1 gene plays an important role in E. coli F18 resistance (Wang et al, 2014). These results are also in agreement with Bao et al (2012).…”
Section: Polymorphism Of the Tap1 Genesupporting
confidence: 74%
See 1 more Smart Citation
“…TAP1 plays a significant role in immune responses because of its increased expression level after infection by viruses and bacteria. Zhao et al (2014) analyzed TAP1 mRNA relative expression levels in 11 tissues from resistant and susceptible phenotypes, and found that the G729A mutation of TAP1 had a significant effect on TAP1 mRNA expression, with high expression possibly conferring resistance against E. coli F18, which confirms that the TAP1 gene plays an important role in E. coli F18 resistance (Wang et al, 2014). These results are also in agreement with Bao et al (2012).…”
Section: Polymorphism Of the Tap1 Genesupporting
confidence: 74%
“…The primer pair used for FUT1 ) amplification was F: 5'-CTTCCTGAACGTCATCAAGACC-3' and R: 5'-CTTCAGCCAGGGCTCCTTTAAG-3' (Sangon, Shanghai, China). The primer pair for TAP1 exon 3 (Sun et al, 2012;Zhao et al, 2014) was F: 5'-GAAATGTGGATAAGAGCA-3' and R: 5'-AAACAGACGGATAATGAAAGAGG-3' (Sangon). Amplification reactions were carried out on 80 to 150 ng genomic DNA in a 50 μL reaction volume containing 48 μL compound pfu PCR buffer (final concentration 1X buffer, 2 mM MgCl 2 , 10 mM each dNTP, 25 μM each primer, and 5 U pfu polymerase; TaKaRa, Dalian, China).…”
Section: Polymerase Chain Reaction-restriction Fragment Length Polymomentioning
confidence: 99%
“…This polybasic loop was proposed to benefit particularly the intestinal binding of F18-ETEC to pig intestines, in the absence of inhibitory milk glycans that follows weaning (210). Several investigators in China detected that the homozygous resistance genotype occurred only in certain western breeds and associated with genotypes for other forms of resistance (211214). …”
Section: Adhesins and Host Receptorsmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) localized on alpha (1,2)-fucosyltransferase (FUT1) and bactericidal/permeability-increasing protein (BPI) genes are responsible for swine F18-ETEC susceptibility [ 10 , 11 , 12 ], while the porcine susceptibility or resistance to F4ac-ETEC is controlled by the Mucin4 (MUC4) and Mucin13 (MUC13) genes [ 13 , 14 , 15 ]. Genetically, some piglets lack the fimbriae receptor genes, and thus may be resistant to ETEC infections [ 1 , 16 ]. The presence or absence of intestinal receptors for ETEC attachment and colonization determines the probability of the piglets developing PWD [ 8 , 17 ].…”
Section: Introductionmentioning
confidence: 99%